THE IMPLEMENTATION OF HEALTH PROTOCOLS ON E-COURT SYSTEMS DURING THE COVID-19 PANDEMIC ERA (In Bandar Lampung City) - Muhammad Fakih; Selvia Oktaviana; Ely Nurlaili; Dita Febrianto; Nilla Nargis (Universitas Lampung, 2022)
The COVID-19 Pandemic has significantly impacted the health sector and the economy. As an affected country, the Indonesian Government has issued many policies to prevent and control the Covid-19 virus. However, substantial problems arise, with the absence of compliance from some people in certain areas, such as Bandar Lampung City, Lampung Province. Although the local Government issued Regional Regulation Number 3 of 2020 concerning Adaptation of New Habits in the Prevention and Control of Corona Virus Disease 2019 to regulate the community's obligations in implementing the 3M are still Health Protocol in public spaces, the main problem in this study is the people of Lampung Province's lack of discipline in implementing the 3M Health Protocol and the dynamics of implementing e-Court during the Pandemic. Therefore, there needs to be a review regarding the effectiveness of implementing the 3M Health Protocol to prevent the spread of Covid-19 in Bandar Lampung, as well as the application of e-Court in the perspective of other laws and regulations. The research method used in this study is empirical law research, taking a problem-based approach to a behavioral approach supported by primary data sourced from data sources. The implementation of the 3M health protocol through Regional Regulation Number 3 of 2020 shows quite effective results in its application in public spaces based on a survey of 86 respondents from the people of Bandar Lampung City. It was recorded that 83.5% of 86 respondents stated that public services at the Court had been carried out online, while 16.5% stated that they were done online through e-Court but limited. However, when taken as a whole, the implementation of health protocols and e-Courts as part of the effort to prevent the spread of Covid-19 is relatively good; it's just that certain obstacles must be evaluated.